The Methodology of Reasoning and Derivation from the Previous Divine Books in “Tafhīm ul Qur’ān” - Muhammad Khubaib; Muhammad Afzal (jihat-ul-islam, 2021)
Syed Abū Āl Ā'la Maudūdī (1903-1979) belongs to a time when Christian missionaries, under the wings of the British rule of the subcontinent, were desperately trying to persuade and compel the Muslim community to convert to Christianity. They were working hard on the agenda to cast doubts on the ideology and beliefs of Muslims. Syed Maudūdī wrote the commentary of Qur’ān "Tafhīm ul Qur’ān" not only for Muslims to adhere to their beliefs but also to invite Christians to Islam in which he dispelled their objections and doubts by arguing from their own holy books. By comparing the Qur’ān and the previous holy books in great detail, he proved that the Qur’ānic traditions are not derived from the teachings of the Jews and Christians, but present their correct form. He has not only refuted the doctrines of Trinity, Sonship and Atonement with strong arguments but also clarified the Qur’ānic supremacy. In this research paper, Syed Maudūdī's Tafhīm ul Qur’ān will explain the style and methodology of reasoning from the previous heavenly books. As a result, dubious minds will be able to adhere to Islamic beliefs and Christians will be able to come closer to Islam.